Accidentally discovered Portal Vein Thrombosis before Splenectomy due to Hypersplenism - The role of Thrombogenic Genes Polymorphisms - Amr Shaaban Hanafy (Archives of Hepatitis Research - Peertechz Publications, 2017)
Portal vein thrombosis in patients with liver cirrhosis may be due neoplastic growth invading portal vein or due to non-neoplastic causes. The indications for treating PVT in cirrhotic individuals are diffi cult to be established but at least are of great benefi t in acute PVT. Investigating the cause of portal vein thrombosis in cirrhotic patient prepared for splenectomy including virology and immune markers, AFP, triphasic CT. Factor V Leiden mutation and prothrombin gene 20210. The case showed non-neoplastic portal vein thrombosis due to portal pyemia with underlying prothrombin gene 20210 polymorphism. The early initiation of anticoagulation after the diagnosis of acute PVT may be the only predictive factor for complete PV recanalization with preservation of liver function.